Rational Poverty or Poor Rationality? The Take-up of Social Assistance Benefits - Regina T. Riphahn (Institute for the Study of Labor (IZA), 2000)
In several countries social assistance dependence has been increasing since the 1980s. After surveying the theoretical and empirical take-up literature, this study presents estimates of recent rates of non take-up of social assistance benefits. Once methodological shortcomings of prior estimations are corrected, the results show that take-up has fallen recently and thus cannot explain the rising welfare receipt. Following theoretical predictions, the probability that a rational individual takes up social assistance increases with the expected benefit amount and duration, and falls with application cost and stigma. More than half of all households eligible for transfers under the German social assistance program did not claim their benefits.
Keywords: I38; D31; I32; 330; Take-up; transfer program; social assistance; welfare; Sozialhilfeempfaenger; Rationales Verhalten; Armut; Schätzung; Deutschland